Corporate social responsibility: tactics for sustainability - Nehme, M. N. (My University, 2020)
Corporate Social Responsibility (CSR) is a modern concept in the field of business ethics and management which attracts governmental bodies and international organizations and companies to adopt it in the recent decade. Thousands of scholars and scientists have transformed the concept of CSR from a philanthropic form into an applied theoretical framework that influence the economic, social and environmental sustainability. However, implementing CSR approaches required several steps that must be done by decision makers inside a company or organization. An accurate description and suggestion for the hierarchal steps that must be followed by decision makers and entrepreneurs to implement CSR in the most efficient way has been suggested through these papers.
Keywords: corporate social responsibility; sustainability; decision making; tactics